CHALLENGES AND OPPORTUNITIES IN IMPLEMENTING PATIENT SAFETY CULTURE ACROSS HEALTHCARE DEPARTMENTS - Sahar Ahmed Abdullah Masoudi, Noora Saleh Alrowaily, Taghreed Mamdouh Salem Alruwaili, Dalal Abdulaziz Atnan Alsaroofi, Afaf Khatam Alrowaily, Wafa Salman Alblowy (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2025)
Patient safety culture is a fundamental component of high-quality healthcare and plays a critical role in reducing preventable harm across all clinical and support departments. Despite global efforts to strengthen safety practices, healthcare organizations continue to face challenges related to communication gaps, inconsistent adherence to safety protocols, staff workload, and variations in safety awareness among multidisciplinary teams. This literature-based paper explores the key challenges that hinder the implementation of a strong patient safety culture—such as resource limitations, reporting barriers, and organizational resistance—while also highlighting existing opportunities including leadership support, safety education, digital reporting systems, and interprofessional collaboration. Understanding these factors is essential for creating a proactive environment where patient safety is prioritized, risks are minimized, and continuous improvement becomes part of daily practice. Strengthening patient safety culture across healthcare departments can significantly enhance clinical outcomes, reduce errors, and promote a safer healthcare system.